ACCURACY OF THE WATCHBP O3 DEVICE FOR AMBULATORY BLOOD PRESSURE MONITORING ACCORDING TO THE NEW CRITERIA OF THE ISO81060–2 2018 PROTOCOL. (April 2021) - Fania, Claudio; Lazzaretto, Ilaria; Fontana, Umberto; Palatini, Paolo
Abstract : Objective: To determine the accuracy of the Microlife WatchBP O3 monitor for ambulatory blood pressure measurement according to the new ISO81060–2 2018 protocol. Design and method: The WatchBP O3 model is an oscillometric fully automatic device for blood pressure measurement at the upper arm. The device accuracy was first tested in 97 subjects from the general population (mean age, 71.3 years; 48 men) over a wide range of arm circumferences using four cuffs of different size suitable for arm circumferences ranging from 14.0 to 52.0 cm. In a second study, 36 subjects (mean age, 72.9 years; 18 men) underwent stress testing on a cycle ergometer in order to increase their heart rate by 15% or more. The new recommendations of the ISO81060–2 2018 protocol were followed. Blood pressure measurement was performed by two observers with binaural stethoscope using the same arm sequential method. Results: In the general population, the mean device–observer difference in the 291 separate blood pressure data pairs was 1.33 ± 3.18 mmHg for systolic blood pressure and was 0.73 ± 3.17 mmHg for diastolic blood pressure. These data were in agreement with criterion 1 of the protocol standard requirements (mean, less than or equal to 5 mmHg; SD, ± 8 mmHg). Also criterion 2 was satisfied being the Standard Deviations of the 97 participants well below the maximum values required by the protocol. During the ambulatory monitoring study, the minimum heart rate increase during exercise stress testing was obtained in all subjects. The average heart rate increase was 20.3% (range 15.4% to 28.9%). The mean device–observer difference in the 108 separate blood pressure data pairs was 1.51 ± 2.79 mmHg for systolic blood pressure and was 1.72 ± 2.58 mmHg for diastolic blood pressure. Also these data were in agreement with criterion 1 of the protocol standard requirements. Conclusions: These data show that the Microlife WatchBP O3 monitor satisfied the ISO 81060–2:2018 standard requirements for a general population across a wide range of arm sizes and that also the protocol criteria for validation of devices intended for ambulatory blood pressure monitoring were fulfilled.